2006
DOI: 10.1111/j.1365-2893.2006.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged antiviral therapy for hepatitis B virus‐infected health care workers: a feasible option to prevent work restriction without jeopardizing patient safety

Abstract: To prevent transmission of hepatitis B virus (HBV) from health care workers (HCWs) to patients, highly viraemic HCWs are often advised to restrict performing exposure prone procedures (EPPs). To prevent loss of highly qualified medical personnel and simultaneously minimize transmission risk to patients, we offered highly viraemic HCWs antiviral therapy and evaluated the effects of this strategy. Eighteen chronic HBV-infected HCWs have been monitored every 3-6 months for a median period of 5.6 years (range 1.1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…60 However, with the availability of inhibitors of HBV polymerase for chronic HBV infection treatment, HBV DNA may be durably suppressed in HBV-infected HCWs. Thus, as illustrated by Buster et al 61 prolonged antiviral therapy for HBV-infected HCWs is a viable option instead of work restriction, provided that the level of HBV DNA is monitored regularly. This option is also likely to encourage already employed HCWs to determine their status.…”
Section: Hbvmentioning
confidence: 96%
See 1 more Smart Citation
“…60 However, with the availability of inhibitors of HBV polymerase for chronic HBV infection treatment, HBV DNA may be durably suppressed in HBV-infected HCWs. Thus, as illustrated by Buster et al 61 prolonged antiviral therapy for HBV-infected HCWs is a viable option instead of work restriction, provided that the level of HBV DNA is monitored regularly. This option is also likely to encourage already employed HCWs to determine their status.…”
Section: Hbvmentioning
confidence: 96%
“…55 Current guidelines concerning prevention of HCW-to-patient transmission of HCV need to be improved. An alternative option to work restrictions for HCV-infected HCWs would be a therapeutic option, 61 which would also incite HCWs to learn their status. In light of the fact that new drugs with increased efficacy will soon be available for patients with chronic hepatitis C, 65 a therapeutic option for HCV-infected HCWs should be strongly encouraged in the near future.…”
Section: Hcvmentioning
confidence: 99%
“…Health care workers who test positive for HBsAg, especially those who are HBeAg‐positive and/or have high levels of serum HBV DNA, may be prohibited from working if they are engaged in exposure‐prone procedures 42, 43. It has been suggested that antiviral treatment should be initiated in such cases to allow these workers to return to work 44. This practice has become common in some European countries where health care workers with serum HBV DNA levels below a certain threshold (varying from 3‐5 log 10 copies/mL) are permitted to return to work provided that surveillance testing shows that HBV DNA levels remain suppressed 43.…”
Section: Other Considerations In Therapymentioning
confidence: 99%
“…More recent HBV inhibitors like entecavir and tenofovir display a much more favourable resistance profile [ 10 , 11 ]. Buster et al have shown that prolonged antiviral therapy for HBV-infected health care workers is a viable option instead of work restriction, provided that the level of HBV DNA is monitored regularly [ 12 ]. Indeed in five cases the ban on EPPs could be lifted, because of successful suppression of HBV.…”
Section: Discussionmentioning
confidence: 99%